Students' Mathematical Literacy in Solving Ethnomathematics-Based Problems Viewed from Self-Efficacy - Widyani, Fitri Anggi; Khotimah, Rita Pramujiyanti (Universitas Wiralodra, 2023)
The purpose of this study is to describe how students' mathematical literacy is in solving ethnomathematics-based questions in terms of student self-efficacy. Three grade VIII students of SMP Negeri 1 Surakarta were selected as samples based on the results of the self-efficacy questionnaire and assigned according to the self-efficacy category. Data collection techniques were carried out using self-efficacy questionnaires, mathematical literacy tests, and interviews. The results of the research that has been done show that students with high self-efficacy categories can fulfill the six indicators of mathematical literacy. Students in the self-efficacy category are being able to solve the questions given, but have not been able to fulfill the indicators of using arithmetic operations and mathematical symbols. Students in the low self-efficacy category were only able to fulfill the communication and mathematization indicators on the three mathematical literacy questions.